2013
DOI: 10.1016/j.rpor.2012.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative radiation therapy as part of breast conserving therapy of early breast cancer—Results of one-year follow-up

Abstract: Due to its exceptional physical and radiobiological properties, intraoperative radiation therapy can be a good alternative to other methods of boosting dose to the post-operative site in management of low stage breast cancer, enabling a precise therapy to the tumour bed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…A total of 88% of postwhole breast irradiation patients had no edema, and this result was comparable to other reports . Electron‐based IORT combined with whole breast irradiation resulted in comparable number of patients without breast edema, although the observation time was 1 year . In the UK IMPORT trial, as in our IORT only group, there were only a few cases of edema in the APBI arm .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A total of 88% of postwhole breast irradiation patients had no edema, and this result was comparable to other reports . Electron‐based IORT combined with whole breast irradiation resulted in comparable number of patients without breast edema, although the observation time was 1 year . In the UK IMPORT trial, as in our IORT only group, there were only a few cases of edema in the APBI arm .…”
Section: Discussionsupporting
confidence: 87%
“…Grade 2 pain was reported more frequently in other studies (6.9% and 10%), whereas in our group only one (1.2%) patient reported it. Wareńczak‐Florczak reported comparable results to ours with electron‐based intraoperative irradiation . Coles et al showed comparable number of patients with no pain post‐APBI irradiation, but more patients (45.7%) reported pain postballoon brachytherapy …”
Section: Discussionsupporting
confidence: 72%
“…Following the two large clinical trial studies on IORT other centers have further reported their institutional experiences with IORT in early stage BC (12)(13)(14). Among which chowdhry et al (15) from the Massachusetts General Hospital reported on 109 patient who received IORT.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological studies on selected women for conservative surgery of the breast have demonstrated that it's improbable that the microscopic extension of the malignant cells reaches more than 1 cm [15] therefore local recurrence very probably develops from the cells that surround the primary tumor and not from additional cancer foci, this suggests that the primary target that requires adjuvant treatment with radiotherapy following a lumpectomy (with negative margins) it's probably limited by a 2 cm area around the borders of the cavity [16]- [18]. Taking that into account to avoid risks of recurrence for single dose treatments we deliver a dose of 20 Gy prescribed at 2 mm, that for instance for a 3.5 cm diameter applicator will deliver a 6.9 Gy at a depth of 1 cm, plus the margins given at the lumpectomy it broadens the area of treatment to include the volume desired.…”
Section: Discussionmentioning
confidence: 99%